2011
DOI: 10.2174/1874155x01105010124
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Synthesis Design and Optimization Analysis on Scroll Profiles for Scroll Vacuum Pump

Abstract: The scroll profile plays a very important role in the design of a scroll vacuum pump in oil filter. Therefore, a geometric general form of the scrolls based on Whewell equation was developed in this study. The general planar curve form of the scrolls was specified using the Whewell equation, which consists of three segments and it is easy to analyze and optimize. The analysis reveals that the general model can contain most scrolls based on circle. A general design and multi-objective optimization process for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The operation tests on the RSTB were carried out under a specific pressure of 0.5 MPa and a temperature of 40 , which revealed that the operation had significant effects on increased onset of vibration and squeal. However, the normal vibration of the rubber influenced the slip velocities and the distribution of frictional forces [15]. In a microscopic range the harmonically oscillating long cylinder sliding on the flat surface of an elastic substrate of the rubber, the time histories of the width of the contact zone and the length of adhesion subzone were partial.…”
Section: Vibration and Squeal Testmentioning
confidence: 99%
“…The operation tests on the RSTB were carried out under a specific pressure of 0.5 MPa and a temperature of 40 , which revealed that the operation had significant effects on increased onset of vibration and squeal. However, the normal vibration of the rubber influenced the slip velocities and the distribution of frictional forces [15]. In a microscopic range the harmonically oscillating long cylinder sliding on the flat surface of an elastic substrate of the rubber, the time histories of the width of the contact zone and the length of adhesion subzone were partial.…”
Section: Vibration and Squeal Testmentioning
confidence: 99%